The Doctrine of Chanted Language in the Chandogya Upanisad - Post, Kenneth Howard (My University, 1977)
The Chandogya Upanisad is one of the most important pieces of literature in orthodox Hinduism. It contains some of the most crucial statements for the religion about salvation and ritualistic uses of language. This dissertation attempts to explain to modern Western readers what the Chandogya Upanisad says about the nature of language and in so doing explain the meaning of the Upanisad. In order to do this the traditional explanations of the text have been considered as carefully as posslble. One aspect of this consideration has been that whereas previous explanations of the text have not considered the implications of the ChU's relation to the Chandogya Brahmana this has. Another aspect has been that whereas previous explanations have not sought to understand this text as a complete and necessary whole this one has.
Consequently part of the dissertation seeks implicitly and explicitly to demarcate the assumptions of previous scholarship from the assumptions of the ChU. The result of this is to show modern scholarship's desire to point out the historicality of the ChU and the ChU's desire to point out the uninformativeness historicality. The paradigmatic case of these incompatible desires is etymology which in the ChU is seen to imply the unity inherent to eternal being and in modern linguistics is seen to be the record of the historicality of beings, in particular, man. Another result of this part of the investigation was to discover that the transmission of upasana's (teachings) was a central cohesive theme of the ChU and that the ritualization of speech was inherent to this transmission.
The central thesis of this dissertation is that chanted or ritualistic language is said in the ChU to be founded in desire which necessarily implies a dependent order of being. Language, which exists within this being, articulates various limits of dependency most authentically in a ritualistic manner. The primordial form of ritualistic speech is the pronoun, tat, which implies that the central phenomenon of all things is that they can be counted. We show during the course of the explanation of this thesis how the ChU points out what this dependency and numericality mean with respect to sacrifice, religious language, etymology, social order, propriety, duty, and education. In so doing we hope to have explained many of the more obscure portions of the text as well as to have presented the context in which several later theological discussions took place in the tradition.
Keywords: Chandogya Upanisad; orthodox Hinduism; nature of language